2021
DOI: 10.3390/ani11071938
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Fecal Microbiota of Grazing Mongolian Cattle from Different Regions in Inner Mongolia, China

Abstract: Mongolian cattle from China have strong adaptability and disease resistance. We aimed to compare the gut microbiota community structure and diversity in grazing Mongolian cattle from different regions in Inner Mongolia and to elucidate the influence of geographical factors on the intestinal microbial community structure. We used high throughput 16S rRNA sequencing to analyze the fecal microbial community and diversity in samples from 60 grazing Mongolian cattle from Hulunbuir Grassland, Xilingol Grassland, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…A number of 417 samples from yak feces were also included for a comprehensive analysis of yak fecal microbiota. We observed a distinctive composition of microbiota between different yak gastrointestinal segments and feces ( Figures 2B–D ), in agreement with the situation observed in other members of the bovine family ( 13 , 14 ). In the microbiota of the yak colon, the most dominant phylum with respect to its relative abundance is Firmicutes (59.05%), followed by Bacteriodetes (28.09%) and proteobacteria (1.26%).…”
Section: Resultssupporting
confidence: 89%
“…A number of 417 samples from yak feces were also included for a comprehensive analysis of yak fecal microbiota. We observed a distinctive composition of microbiota between different yak gastrointestinal segments and feces ( Figures 2B–D ), in agreement with the situation observed in other members of the bovine family ( 13 , 14 ). In the microbiota of the yak colon, the most dominant phylum with respect to its relative abundance is Firmicutes (59.05%), followed by Bacteriodetes (28.09%) and proteobacteria (1.26%).…”
Section: Resultssupporting
confidence: 89%
“…This study indicated that Firmicutes , Bacteroidetes , Ascomycota and Basidiomycota were the most preponderant microbial phyla in yaks, regardless of health status, which was in line with previous investigations on yaks [ 24 ]. Additionally, these dominant phyla were also demonstrated to be extensively existed in the goats, giraffes and cattle, indicating their importance in intestinal ecology and functions in ruminants [ 31 , 41 ]. Some specific bacterial and fungal alternations may reflect the potential relationship between diarrhea and gut microbiota, thus we further characterized the intestinal bacteria and fungi associated with diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…The composition and diversity of the gut microbiota are affected by biotic and abiotic factors, such as genetic background, diet, season, region, habitat, and other environmental factors ( e.g. , Xin et al, 2019 ; Chang et al, 2020 ; Fan et al, 2020 ; Aricha et al, 2021 ; Guo et al, 2021 ; Ilina et al, 2021 ; Jiang et al, 2022 ), but diet is considered one of the predominant factors influencing the diversity and composition of the gut microbial community ( Kim et al, 2014 ; Khafipour et al, 2016 ; Guo et al, 2021 ; Wei et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%